Experimental study on mechanical properties and durability of basalt fiber reinforced coral aggregate concrete. (20th March 2020) - Niu, Ditao; Su, Li; Luo, Yang; Huang, Daguan; Luo, Daming
Highlights: The effects of BF on the mechanical properties of CAC at different curing ages are studied. Detailed chloride contents brought by coral aggregates of BFRCAC are recorded, including total and free chloride content. Water absorption and sorptivity properties of BFRCAC are investigated. TG-DTG and FE-SEM are used to study microstructure of BFRCAC. Abstract: With the development of marine technology, the potential of coral aggregate concrete (CAC) for use in the construction of reefs has been identified. However, the shape, surface structure, high porosity, and chloride-ion-carrying properties of coral aggregates yield special microstructures and affect the mechanical properties and durability of CAC. This study investigates the effect of basalt fiber (BF) on the mechanical properties, chloride content carried in coral aggregates, and water absorption of CAC. The results indicate that with the increase in fiber content, the mechanical properties and water absorption resistance of basalt fiber reinforced coral aggregate concrete present an increasing trend then followed decreasing trend. Furthermore, 0.05% BF yields the highest improving effect on the mechanical properties and water absorption resistance at 28 days. Compared with the reference concrete, the compressive strength and splitting tensile strength of CAC with 0.05% BF increase by 9.87% and 1.36% at 28 days, respectively. When the fiber content continues to increase, the strengthening effect decreases, and cause adverse effects. The dissolution of chloride in coral aggregates was accelerated by 0.05% BF, while the chloride dissolution was inhibited by 0.1%–0.2% BF. Moreover, the microstructure of CAC is investigated to elucidate the enhancement mechanism of BF in terms of thermogravimetric analysis, theoretical total pore volume, fiber bonding performance, and fiber-matrix interfacial characteristics.